Pengaruh Qr & Dar Terhadap NPL Pada Bank Central Asia (BCA) Periode 2013 – 2023 - Sabyla Chandra Juniar; Uchi Octavia; Suparjono (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the effect of Quick Ratio (QR) and Debt to Asset Ratio (DAR) on the level of Non-Performing Loan (NPL) at Bank Central Asia (BCA). Quick Ratio is used to measure bank liquidity in meeting short-term obligations, while Debt to Asset Ratio indicates the structure of capital and the risk of bank solvency. The data used is the financial statements of BCA Bank during a certain period which is analyzed using quantitative methods with multiple linear regression techniques. The results showed that Quick Ratio has no significant effect on NPL, while Debt to Asset Ratio has a negative and significant effect on NPL. This indicates that the better the management of the bank's capital structure, the lower the risk of non-performing loans. These findings provide important implications for risk management and liquidity management in the banking sector, especially at BCA Bank.